Relasi Birrul Walidain dengan Kesuksesan Karir Anak (Kajian Tematik Konseptual) - Sri Widad Safitri; Ridwan Hasbi; Afrizal Nur (Syntax Corporation Indonesia, 2024)
The purpose of this article is to propose a relation between filial piety towards parents and a child's career success. The research methodology employed is contextual thematic analysis, focusing on verses of filial piety (Birrul Walidain) found in al-Isra’:23-24, Luqman:14, and al-Ahqaf:15. Interpretations used for dissecting these verses include the social-adab style commentaries by renowned scholars such as HAMKA's Al-Azhar, Hasbi Ash-Shiddieqy's An-Nur, and Ahmad Musthafa Al-Maraghi's Al-Maraghi. HAMKA's interpretation states that, regardless of one's job position, be it an official/police officer/doctor/successful entrepreneur, one must not forget their parents and continually show filial piety towards them. Hasbi Ash-Shiddieqy emphasizes that being a filial child entails not only being dutiful while parents are alive but also continuing to fulfill filial duties even after their passing, ensuring the child's obedience to Allah for the well-being of their parents. Al-Maraghi, through his commentary on the filial piety verses, relates the command to express gratitude by being dutiful to parents to the success and progress of the child, indicating the positive influence of the parents. This serves as evidence of the virtue of a filial child, impacting not only their spiritual relationship with Allah but also providing tangible benefits in worldly life which is the child's career success.